Precise genome editing in the silkworm Bombyx mori using TALENs and ds- and ssDNA donors - A practical approach - Takasu, Yoko; Kobayashi, Isao; Tamura, Toshiki; Uchino, Keiro; Sezutsu, Hideki; Zurovec, Michal (Insect biochemistry and molecular biology, 2016)
Engineered nucleases are able to introduce double stranded breaks at desired genomic locations. The breaks can be repaired by an error-prone non-homologous end joining (NHEJ) mechanism, or the repair process can be exploited to introduce precise DNA modifications by homology-directed repair (HDR) when provided with a suitable donor template. We designed a series of DNA donors including long dsDNA plasmids as well as short ssDNA oligonucleotides and compared the effectiveness of their utilization during gene targeting with highly efficient transcription activator-like effector nucleases (TALENs). While the use of long dsDNA donors for the incorporation of larger DNA fragments in Bombyx is still a problem, short single-stranded oligodeoxynucleotides (ssODNs) are incorporated quite efficiently. We show that appropriately designed ssODNs were integrated into germ cells in up to 79% of microinjected individuals and describe in more detail the conditions for the precise genome editing of Bombyx genes. We specify the donor sequence requirements that affected knock-in efficiency, and demonstrate the successful applications of this method of sequence deletion, insertion and replacement in the Bombyx genome.
Keywords: bourec; TALENs; Animals; Transcription Activator-Like Effector Nucleases; DNA, Single-Stranded; DNA; zvířata; editace genu; jednovláknová DNA; Bombyx; Gene Editing